Anticipation in familial Crohn's disease. Issue 2 (1st February 1998) - Grandbastien, B; Peeters, M; Franchimont, D; Gower-Rousseau, C; Speckel, D; Rutgeerts, P; Belaïche, J; Cortot, A; Vlietinck, R; Colombel, J-F
Abstract : Background —Offspring with a family history of Crohn's disease have an earlier age of onset than their parents. This might be due to genetic anticipation, characterised by earlier and/or more severe disease in subsequent generations. Aims —To investigate the possibility of genetic anticipation in affected parent-child pairs with Crohn's disease from France and Belgium. Patients and methods —In a cohort of 160 multiply affected families with Crohn's disease, 57 parent-first affected child pairs were detected. Clinical characteristics (age at diagnosis, disease extent, and type) of both parents and children were registered and compared. Results —Children were younger than their parents at diagnosis in 48/57 (84%) pairs. The median age at diagnosis was 16 years younger in children than in parents (p<0.0001). However, the difference was related to the age at diagnosis in the parents and was not present in 12 parent-child pairs with an early age at diagnosis for the parents. In most cases, disease extent and type were not considered more severe in children than in parents. Parental sex affected neither age at diagnosis nor extent and type of disease in children. Conclusion —Patients in the second affected generation acquire their disease at an earlier time in life in some but not all familial cases of Crohn's disease. Several explanations including genetic anticipation and environmental factors might explain this phenomenon.